EFFECT OF CHLOROPHYLLIN, AN SEMI-SYNTHETIC CHLOROPHYLL MOLECULE ON HYPERGLYCEMIA AND HYPERLIPIDEMIA IN STREPTOZOTOCIN INDUCED DIABETIC MICE - Patar, Abani K.; Bhan, Surya; Syiem, Donkupar (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The aim of the present study was to determine the effect of chlorophyllin (CHL) on hyperglycemia and hyperlipidemia in streptozotocin (STZ) induced diabetic mice. Methods: Diabetes was induced in mice by administering 150 mg/kg body weight (bw) dose of STZ. The effect of 10, 25, 50 and 100 mg/kg bw doses of CHL on hyperglycemia was examined in diabetic mice for the acute and sub-acute period. The intraperitoneal glucose tolerance test (IPGTT) was performed in diabetic (Group A) as well as diabetic treated with CHL (Group B), metformin (Group C), glibenclamide (Group D), and insulin (Group E) groups. The percent glycosylated hemoglobin (GHb%) level, lipid profile, and atherogenic index (AI) were determined in normal (Group A), diabetic (Group B) as well as diabetic treated with CHL (Group C), and metformin (Group D) groups. Results: In both acute and sub-acute antihyperglycemic study, 50 mg/kg bw dose of CHL was found effective in reduction of blood glucose level significantly and considered as an optimum dose. In IPGTT, the significant reduction of blood glucose level in Group B was observed at 2 h (h) and 4 h in comparison with Group A. The GHb%, lipid profile and AI value of Group C were found significantly different from Group B in the study. Conclusion: The present study justifies the antihyperglycemic and antihyperlipidemic effects of CHL in STZ induced diabetic mice, hence suggesting its beneficial effect in the treatment of diabetes.Â